Gestión de ventas en la empresa Ferretería Gaibor - Cabezas Peñafiel, Kimberly Janeth (2021)
In the period that the pandemic was manifested by the Covid-19 virus, the company "Ferretería Gaibor " took new sales policies to achieve that their products are sold and in this way not to lose their customers, the company was perfected and changed its way of sale, transmitting security and reliability, with the sole purpose of obtaining favorable results to maintain the stability of its business. Qualitative and quantitative methodology was used for the present research, qualitative methodology helped to understand the social phenomenon and its characteristics, while the Quantitative method helped to detail which were the results obtained through the balance sheet and the statement of result where it was reflected a considerable decrease in sales, the application of two financial reasons such as inventory rotation and profit margin. It can be concluded that the pandemic significantly affected sales in 2020 compared to 2019, being this one of the fundamental factors that helped and identified the shortcomings obtained by the Company “ferretería Gaibor”, which will help us to implement new management and sales strategies.